Avaliação do SONAR: análise de motivação de evasão de um serviço de disseminação seletiva de informações do ponto de vista de seus ex-usuários - Monteiro, Vânia da Silva (1988)
The factors influencing the exit of users from SONAR/INIS, an SDI - selective dissemination of information service, are studied. A questionaire has been applied to a sample of 306 ex-users, who have been disconnected between May 1984 and May 1986. Variables referring to standards of information use and users environmental characteristics and formation have been isolated, Fourteen hypotheses, linking the studied variables to the !staying with the service" factor are drawn. Eight hypotheses have been refused while six have been confirmed.